Elements of a riot: forms of political violence in contemporary France. Issue 4 (8th August 2022) - Castañeda, Ernesto
Abstract : This article looks at the aftermath of riots in a suburban area of Paris to make a larger argument about what produces riots, the role of police violence, the activation of social boundaries, and the implied set of demands during and after riots. It uses the methods of visual sociology to show how youth often target symbols of the state to respond to state violence in an asymmetrical confrontation when they feel they do not have a political voice or representation. It also presents original survey data about what non-riot participants think causes these riots. Finally, it shows images from campaigns to ban chokeholds in France, which recent protests have achieved .